Pengaruh Sosialisasi Mitigasi Tanah Longsor dengan Video Animasi Terhadap Tingkat Pengetahuan Warga Krajan Tulakan Pacitan - Belinda Ayu Dewanti; Erika Dewi N (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Landslide is the process of mass transfer of rock or soil due to gravity or gravity. Pacitan Regency is one of the districts that are prone to landslides. The number of landslides in Tulakan District was 59 times. Heavy rain that flushed the Tulakan area was one of the causes of landslides. The purpose of this study was to determine the effect of socialization of landslide disaster mitigation with animated videos on the level of knowledge of the residents of the Krajan Tulakan hamlet, Pacitan Regency. This type of research is quantitative by design quasi-experimental The design used pre and post-test without control. Sampling technique using simple random side. The number of samples in this study was 73 respondents. The research instrument used a questionnaire and an animated video. Data analysis used univariate and bivariate analysis. The statistical test in this study used the test Wilcoxon. Research results with TestWilcoxonresults obtained value is 0.000 < 0.05. The conclusion of this study is that there is an effect of Socialization of Landslide Disaster Mitigation with Animated Videos on the Knowledge Level of Residents in Krajan Tulakan Hamlet, Pacitan Regency